2014
DOI: 10.1371/journal.pone.0096552
|View full text |Cite
|
Sign up to set email alerts
|

Crude Oil Treatment Leads to Shift of Bacterial Communities in Soils from the Deep Active Layer and Upper Permafrost along the China-Russia Crude Oil Pipeline Route

Abstract: The buried China-Russia Crude Oil Pipeline (CRCOP) across the permafrost-associated cold ecosystem in northeastern China carries a risk of contamination to the deep active layers and upper permafrost in case of accidental rupture of the embedded pipeline or migration of oil spills. As many soil microbes are capable of degrading petroleum, knowledge about the intrinsic degraders and the microbial dynamics in the deep subsurface could extend our understanding of the application of in-situ bioremediation. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
53
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(69 citation statements)
references
References 58 publications
11
53
1
1
Order By: Relevance
“…We found that crude oil 318 had a deleterious effect on microbial alpha-diversity (Tables 2 and 3). This result is 319 similar to that obtained by Yang (2014), as crude oil was thought to have an eco-320 toxicological effect. The higher amount of CO 2 evolved in the crude oil treated-soil 321 (Figure 2) is related to the oil stressing effect (Franco et al, 2004), and the further peaks 322 observed in the Figure 2, might be related to different fractions of oil being degraded 323 according to its bioavailability.…”
Section: Discussion 316supporting
confidence: 74%
“…We found that crude oil 318 had a deleterious effect on microbial alpha-diversity (Tables 2 and 3). This result is 319 similar to that obtained by Yang (2014), as crude oil was thought to have an eco-320 toxicological effect. The higher amount of CO 2 evolved in the crude oil treated-soil 321 (Figure 2) is related to the oil stressing effect (Franco et al, 2004), and the further peaks 322 observed in the Figure 2, might be related to different fractions of oil being degraded 323 according to its bioavailability.…”
Section: Discussion 316supporting
confidence: 74%
“…For instance, the percentages of oil degradation by Penicillium chrysogenum at 26, 28, 31 and 37°C were 30.3 %, 43.8 %, 43.2 % and 15 %, respectively (Goddy and Dami 2013). However, the biodegradation of hydrocarbons in psychrophilic environments have been also reported (Sizhong et al 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Sphingomonadaceae, Caulobacteraceae, and Rhodospirillaceae (Alphaproteobacteria), Alcaligenaceae, Comamonadaceae, and Burkholderiaceae (Betaproteobacteria), Pseudomonadaceae and Xanthomonadaceae (Gammaproteobacteria), and Nocardiaceae (Actinobacteria), among others, have been reported to be enriched during hydrocarbon degradation (5,55,56). Bacteroidetes may become enriched in creosote-contaminated soils, in which PAHs are main pollutants (7).…”
Section: Fig 2 Effect Of Diesel Pollution and Bioremediation Treatmenmentioning
confidence: 99%